(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2024)
This article examines the embedding of iingoma and izibongo as valuable historical sources that should be utilised by educators in history classrooms in South African secondary schools. It shows how these sources can be used effectively by history teachers to re-enact the past in the classroom. Interviews with elderly people and iimbongi as well as written sources showed that traditional songs and izibongo are valuable historical sources that can be used to present a balanced account of the past in the classroom. Iimbongi claim that the use of izibongo in teaching history enhances understanding of South African history. Thus, iimbongi gave their own perspective on the significance and implications of employing izibongo as historical sources in the decolonisation of history. Written sources and interviews with iimbongi and elderly people were used as a basis for arriving at why and how sources like iingoma and izibongo may be incorporated into the history classroom to decolonise South African history. Using these historical sources in the teaching and learning of history helps to present different perspectives on the history of South Africa. The incorporation of iingoma, freedom songs, and izibongo in the Further Education and Training (FET) phase, as well as in Social Sciences, is a strategy to acknowledge and address the biases that exist in written history. It became evident that there is a link between written history on the one hand, and iingoma and izibongo on the other hand. The link is critical for engaging in the process of transforming and decolonising South African history. It is recommended that the Department of Basic Education (DBE) should conduct in-service training/workshops for history teachers.